Assessing Students' Learning Attitude and Academic Performance Through m-Learning During the COVID-19 Pandemic - Bamidele Aremu; Olufemi Adeoluwa (The Canadian Network for Innovation in Education (CNIE), 2022)
This study aimed to assess college of education students' learning attitude and academic performance in using m-learning during the COVID-19 pandemic. The study employed a pre-test and post-test experimental research design with 50 students from the College of Education, Ikere Ekiti, Nigeria. Two research instruments were used to collect data from the participants on two occasions. The first instrument was a students' attitude questionnaire that measured the attitude of the participants towards learning. The second instrument was the students' academic performance test that measured the students' scores. The differences between pre- and post-tests were measured through independent t-test. Demographic data are presented in a bar chart and show that the majority of the students own mobile devices that were suitable for learning; that the majority of the students used mobile devices for learning; and that all the respondents in the experimental group possessed mobile devices with the Zoom app. The pre-test findings revealed no significant differences in the attitude and performance of students towards m-learning and traditional learning (p>0.005) while the post-test findings showed significant differences in the attitude and performance of students towards m-learning and traditional learning (p<0.005). These findings suggest that m-learning should be integrated into the school curriculum.